2012
DOI: 10.1111/j.1745-3933.2011.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

A time-variable, phase-dependent emission line in the X-ray spectrum of the isolated neutron star RX J0822−4300

Abstract: RX J0822-4300 is the central compact object associated with the Puppis A supernova remnant. Previous X-ray observations suggested RX J0822-4300 to be a young neutron star with a weak dipole field and a peculiar surface temperature distribution dominated by two antipodal spots with different temperatures and sizes. An emission line at 0.8 keV was also detected. We performed a very deep (130-ks) observation with XMM-Newton, which allowed us to study in detail the phase-resolved properties of RX J0822-4300. Our n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Lastly, the thermal evolution during the re-emergence phase in the hidden MF scenario can yield to totally different degrees of anisotropy in the surface temperature, depending on the initial MF and the accreted mass. A hidden magnetar with a large, extended toroidal field buried in the crust could qualitatively explain the surface temperature anisotropies inferred in several CCOs: the large pulsed fraction observed in Kes 79 Shabaltas & Lai 2012), the antipodal hotspots seen in Puppis A (de Luca et al 2012) and the small emitting region of the blackbody components needed to fit the spectra of 1E 1207 (De Luca et al 2004). Instead, the weaker (or less extended) hidden toroidal MF provides low pulsed fractions.…”
Section: F I Na L R E M a R K Smentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the thermal evolution during the re-emergence phase in the hidden MF scenario can yield to totally different degrees of anisotropy in the surface temperature, depending on the initial MF and the accreted mass. A hidden magnetar with a large, extended toroidal field buried in the crust could qualitatively explain the surface temperature anisotropies inferred in several CCOs: the large pulsed fraction observed in Kes 79 Shabaltas & Lai 2012), the antipodal hotspots seen in Puppis A (de Luca et al 2012) and the small emitting region of the blackbody components needed to fit the spectra of 1E 1207 (De Luca et al 2004). Instead, the weaker (or less extended) hidden toroidal MF provides low pulsed fractions.…”
Section: F I Na L R E M a R K Smentioning
confidence: 99%
“…For Kes 79, reported a period derivative ofṖ 8.7 × 10 −18 s s −1 ; for 1E 1207, Halpern & Gotthelf (2011) gave two equally good timing solutions, witḣ P = 2.23 × 10 −17 and 1.27 × 10 −16 s s −1 . Only an upper limiṫ P < 3.5 × 10 −16 s s −1 is available for the CCO in Puppis A (Gotthelf, Perna & Halpern 2010;de Luca et al 2012). Applying the classical dipole-braking formula gives an estimate for the dipolar component of the external magnetic field (MF) of B p ∼ 10 10 -10 11 G (at the pole).…”
Section: Introductionmentioning
confidence: 99%
“…XMM-Newton observations showed that the centroid energy of an emission line visible in its X-ray spectrum decreased from 0.8 keV in 2001 to 0.73 keV in 2009-2010 [27]. RX J0822-4300 belongs to a small group of sources known as Central Compact Objects (CCOs).…”
Section: Magnetars With Low External Fieldmentioning
confidence: 99%
“…We note that the (candidate) emission line seen in Puppis A has decreased in energy by 10% in 8.5 yr (De Luca et al 2012); if this is associated with a decaying magnetic field, then a purely crustal field is implied, although the decay may be too rapid. We also note that optical/IR observations of 1E 1207 place a limit of ∆M < 10 −6 M ⊙ on the initial mass of a debris disk (De Luca et al 2011).…”
Section: Modeling Magnetic Field Evolutionmentioning
confidence: 81%
“…The second method involves spectral measurements, i.e., identifying features in the neutron star spectrum with particular magnetic processes. Puppis A has a possible emission line at 0.7−0.8 keV (Gotthelf & Halpern 2009;De Luca et al 2012), and 1E 1207 has broad absorption lines at 0.7 and 1.4 keV (Sanwal et al 2002;Bignami et al 2003). If we assume that a spectral line at energy E is due to electron cyclotron resonance, then the magnetic field is B = 10 11 G (E/1.16 keV)(1 + z g ), where 1…”
Section: Magnetic Field Of Ccosmentioning
confidence: 99%